New targeted treatments for cutaneous T-cell Lymphomas - Martine Bagot (Wolters Kluwer Medknow Publications, 2017)
Cutaneous T-cell lymphomas (CTCLs) represent a group of rare and heterogeneous diseases that are very difficult to treat at advanced stages. The development of monoclonal antibodies is a new hope for the treatment of these diseases. Alemtuzumab (Campath) is a humanized IgG1 kappa monoclonal antibody specific for CD52, an antigen expressed by most T and B lymphocytes. Alemtuzumab may frequently induce long-term remissions in patients with Sezary syndrome but high-dose treatments lead to severe cytopenia, immune depletion, and opportunistic infections. This treatment is less efficient in mycosis fungoides (MF). Brentuximab vedotin is a chimeric anti-CD30 monoclonal antibody conjugated to monomethyl auristatin E, a cytotoxic antitubulin agent. Brentuximab vedotin is a very interesting new treatment for advanced tumor MF, Sezary syndrome, and primary cutaneous CD30+ lymphoproliferative disorders. The main limiting adverse event is neurosensitive peripheral neuropathy. Mogamulizumab is a humanized anti-C-C chemokine receptor Type 4 monoclonal antibody with a defucosylated Fc region leading to increased antibody-dependent cellular cytotoxicity. Mogamulizumab is very efficient on aggressive peripheral T-cell lymphomas, particularly adult T-cell leukemia/lymphoma and CTCLs, especially on the blood component of tumor cells. The main limiting events are related to the concomitant depletion of regulatory T-cells. IPH4102 is a humanized monoclonal antibody that targets the immune receptor KIR3DL2/CD158k. Preclinical results with this antibody offer proofs of concept for the clinical development of IPH4102 to treat patients with advanced CTCL.